Chloride levels in biomass sorghum due to fertilization sources - Martinez Uribe, Raúl Andres [UNESP]; Silvério, Patrícia Chiara; Gravatim Costa, Gustavo Henrique; Nogueira, Lucas Conegundes; Rosa Leite, Lucas Aparecido [UNESP] (Elsevier, 2020)
The Brazilian energy matrix has 43.5% of renewable sources, a higher value than registered in the rest of the world (14%). The sugarcane bagasse used in sugarcane plants underlines the importance of this, which is the second-largest renewable source (17%) in this market segmentation, however, the installed systems could be better used in the offseason with alternative crops such as biomass sorghum (Sorghum bicolor L. Moench), which has a low production cost, short cycle, and high biomass yield. However, this alternative has shown a drawback: the presence of chloride in the biomass, which at the high temperature promotes corrosion of the boilers. Thus, the influence of different potassium fertilization and the harvest times of biomass sorghum on chloride levels in the final biomass were evaluated. The experiment was carried out in the state of São Paulo (Brazil), on the 2015/2016 harvest, using the Palo Alto® hybrid. A randomized block design with 4 replications was used, with 3 treatments for potassium sources (KCl, K2SO4, KNO3) in fertilization and 4 treatments related to harvest times (pre-flowering, flowering, milk grain, hard grain) in a factorial scheme. The results showed that the sources of fertilization do not affect productivity, however, when using KCl there are higher levels of chloride in the final biomass, therefore potassium sulfate or nitrate are better alternatives. The time with the lowest chloride level in the biomass is in the milk grain stage, positively correlating with the time of the highest dry matter production per hectare (38.35 Mg ha−1).
Keywords: Bioelectricity; Bioenergy; Boilers; Chemical analysis; Corrosion; Sorghum bicolor